Transnationalising Jamaah Islamiyyah - Syaifudin Zuhri (Al-Jami'ah Research Centre, 2010)
This article attempts to historically analyse the emergence of transnational jihadist movements in Indonesia, focusing on Jamaah Islamiyyah (JI), which is allegedly responsible for a number of terror attacks in South East Asia. The article discusses the historical background of the emergence of Jamaah Islamiyyah and its current development. It is argued that the Afghan battle-field was an important event and locus for Indonesian jihadits groups to exercise their military capabilities, establish secure bases and subsequently pave the emergence of the transnational jihadist. Through informal networks and joint operations, Jamaah Islamiyyah has become the hub for jihadist movements in Southeast Asia. It was the political opportunity of the reformation which gave way to the public appearance of Jamaah Islamiyyah as the MMI demonstrated, but it also brought the consequence of a split among JI activists. The split reappears when the MMI was becoming involved in politics, and the resignation of Ba’asyir from the top position of the MMI in 2008 exemplifies the turning point to the ideological foundation of JI as the Pedoman Umum Perjuangan Jamaah Islamiyyah (PUPJI) prescribed.